Hydrogen-rich gas production from wet biomass steam gasification with CaO/MgO. (3rd August 2015) - Zhang, Bo; Zhang, Li; Yang, Zhongqing; Yan, Yunfei; Pu, Ge; Guo, Mingnv
Abstract This study investigated the hydrogen production during steam gasification with biomass and a novel sorbent. The biomass sample originated from Ficus lacor leaves with a moisture content of 35 wt.%. The sorbent was prepared by heating the mixture of pre-calcined dolomite, limestone and water at 850 °C for 3 h. Gasification experiments were carried out in a fixed-bed system to study the potential of hydrogen production from steam gasification of wet biomass with the sorbent. The results showed that sorbent with a mass ratio of 1 demonstrated the highest activity toward hydrogen production. This finding must be due to its higher BET surface area. With increasing gasification temperature from 450 to 950 °C, highest hydrogen yield (204.6 ml/g-biomass) was achieved at 850 °C. Steam to biomass mass ratio of 0.5 and sorbent to biomass mass ratio of 0.7 seemed to be optimal during gasification. The enhancement decreased rapidly after the sorbent was repeated regeneration because of sintering and aggregation.